Recent developments in EU law on migration: the legislative patchwork and the Court approach. - Groenendijk, Kees (2014)
More than fifty years passed since the first rules on free movement of workers and self-employed persons in the EEC Treaty (1957) and the first Regulation No. 15 on the free movement of workers (1961) were adopted.